The interfacial twin boundary phases tailored by β-stabilizers in β-Ti alloys: A first-principles study. (1st July 2023) - Zhang, Wen-Yu; Chen, Qiu-Jie; Ma, Shang-Yi; Wang, Shao-Qing
Abstracts: The origins of interfacial twin boundary (ITB) phases at 112 〈 111 〉 β and 332 〈 113 〉 β twin boundaries (TBs) in β-Ti alloys are not well characterized yet. In this work, the local structural features of TBs plus ITB-ω and ITB-α″ phases are carefully investigated with first-principles calculations. It shows the formation of ITB-ω at ( 112 ) [ 11 1 ¯ ] β and ( 332 ) [ 11 3 ¯ ] β TBs are favorable in kinetics, especially the former is further favorable in interfacial energy. Both ITB-ω phases are internally driven by the energy reduction induced by the β→ω transformation. Whereas, the formation of ITB-α″ at ( 332 ) [ 11 3 ¯ ] β TB is infeasible in kinetics and the ITB-α″ is most likely the accompanying or untransformed α″ particle assisting ( 332 ) [ 11 3 ¯ ] β twinning. The formation of ITB phases are highly associated with the types and concentrations of β-stabilizers. The origins and how the ITB-ω and ITB-α″ can be tailored by the β-stabilizers of Mo, Nb and V are clearly demonstrated. Graphical abstract: Image, graphical abstract